Resilient Antarctic monsoonal climate prevented ice growth during the Eocene - Baatsen, Michiel; Bijl, Peter; Heydt, Anna; Sluijs, Appy; Dijkstra, Henk (Climate of the Past, 2024)
Understanding the extreme greenhouse of the Eocene (56–34 Ma) is key to anticipating potential future conditions. While providing an end member towards a distant high-emission scenario, the Eocene climate also challenges the different tools at hand to reconstruct such conditions. Besides remaining uncertainty regarding the conditions under which the large-scale glaciation of Antarctica took place, there is poor understanding of how most of the continent remained ice free throughout the Eocene across a wide range of global temperatures. Seemingly contradictory indications of ice and thriving vegetation complicate efforts to explain the Antarctic Eocene climate. We use global climate model simulations to show that extreme seasonality mostly limited ice growth, mainly through high summer temperatures. Without ice sheets, much of the Antarctic continent had monsoonal conditions. Perennially mild and wet conditions along Antarctic coastlines are consistent with vegetation reconstructions, while extreme seasonality over the continental interior promoted intense weathering shown in proxy records. The results can thus explain the coexistence of warm and wet conditions in some regions, with small ice caps forming near the coast. The resilience of the climate regimes seen in these simulations agrees with the longevity of warm Antarctic conditions during the Eocene but also challenges our view of glacial inception.